Ionic liquid-aided hydrothermal treatment of lignocellulose for the synergistic outputs of carbon dots and enhanced enzymatic hydrolysis. (June 2020) - Xu, Jikun; Dai, Lin; Zhang, Chuntao; Gui, Yang; Yuan, Lan; Lei, Yang; Fan, Baoan
Graphical abstract: Highlights: IL-aided autohydrolysis of straw to produce CDs, digestible cellulose and lignin. The yield of prebiotic XOS with low DP of 2–6 accounted for 14.83% (w/w) of xylan. An in-depth check of autohydrolysate sheds light on the rational design of CDs. The graphite N-doped CDs with bright-blue fluorescence from waste autohydrolysate. An ally of improved digestibility and lignin recovery to revive hydrothermal route. Abstract: How to propel an efficient exploitation of waste streams is a pivotal tache for the long-range augment of hydrothermal biomass valorization. A facile approach was proposed to simultaneously produce carbon dots (CDs), fermentable sugar, and cellulose enzymatic lignin from agricultural straw with the aid of ionic liquid (IL, 1-aminoethyl-3-methylimidazolium nitrate, [C2 NH2 MIm][NO3 ]) catalyzed hydrothermal treatment. The graphite N-doped CDs with bright-blue fluorescence, which was mainly derived from the incorporation of hemicellulose ( e.g. xylooligosaccharides), lignin and [C2 NH2 MIm][NO3 ], exhibited an average-diameter of 8.14 nm. The exfoliation of amorphous parts and robust fibers was formed to improve cellulose digestibility from 14.7 to 81.6%. The efficient recovery and checkup of lignin pave a way for its potential depolymerization into arenes. This protocol offers a significant benefit for large-scale hydrothermal biorefinery where reduction of process waste is a prime concern, and leads to high-value products ( i.e., CDs and lignin) that also fosters the feasibility of bioethanol.